Reviews - Kristiansen, Kristian; Madsen, Bo; Christensen, Charlie (Journal of Danish Archaeology, 1988)
Reviews: G. de G. Sieveking & M. B. Hart (eds.): The Scientific study of flint and chert (by Bo Madsen) K.-E. Behre (ed.): Anthropogenic Indicators in Pollen Diagrams (by Charlie Christensen) C. Renfrew: Archaeology and Language (by K. Kristiansen) K. Raddatz: Der Thorsberger Moorfund. Katalog (by M. 0rsnes) K. Kristiansen (ed.): Archaeological Formation Processes (by M. Coles) P. Ucko: Academic Freedom and Apartheid (by K. Kristiansen) Fennoscandia Archaeologica (by Svend Nielsen) Documents d’archeologie francaise (by P. 0. Nielsen)